2018
DOI: 10.15446/agron.colomb.v36n2.67167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation suspension on the growth, water state and production of spinach (Spinacia olerácea L.) plants

Abstract: Spinach is susceptible to drought conditions, and, because of climate change, it is necessary to optimize water application to crops. Therefore, a test was carried out in a completely randomized design (CRD) with four treatments consisting of the following irrigation suspension durations: T1: 0 d, T2: 4 d, T3: 7 d and T4: 10, with six replicates for a total of 24 experiment units (EU). Each EU consisted of 6 plants, for a total of 120 plants that were transplanted to 2 L pots with a mixture of peat and soil (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The decrease in turgor pressure causes cell development to be one of the physiological processes most vulnerable to water stress decline, either a decrease in cell expansion or inhibition of cell division that contributes to the plant's height. This also goes well with what was found in the previous research study, where the reduction in cellular turgidity and CO 2 uptake once plants are subjected to a water shortage causes the plant to grow slowly and have a low photosynthetic rate, which in return results in poor plant development and lesser dry mass accumulation (Reyes et al, 2018). According to a previous study by Maseko et al (2019), a further increase in water application to 100% ETc (water crop requirement based on evapotranspiration) (47 cm) does not significantly enhance plant height during the first season in Amaranthus cruentus plant.…”
Section: Plant Heightsupporting
confidence: 91%
See 2 more Smart Citations
“…The decrease in turgor pressure causes cell development to be one of the physiological processes most vulnerable to water stress decline, either a decrease in cell expansion or inhibition of cell division that contributes to the plant's height. This also goes well with what was found in the previous research study, where the reduction in cellular turgidity and CO 2 uptake once plants are subjected to a water shortage causes the plant to grow slowly and have a low photosynthetic rate, which in return results in poor plant development and lesser dry mass accumulation (Reyes et al, 2018). According to a previous study by Maseko et al (2019), a further increase in water application to 100% ETc (water crop requirement based on evapotranspiration) (47 cm) does not significantly enhance plant height during the first season in Amaranthus cruentus plant.…”
Section: Plant Heightsupporting
confidence: 91%
“…3, week 3 shows that there are not quite significant differences. At the same time, another study addresses that despite being exposed to particular levels of water stress, plants do not exhibit changes in chlorophyll synthesis (Reyes et al, 2018). It might be because plants are transplanted into 2 L pots with a mixture of peat and soil (2:1), so they remain moist.…”
Section: Chlorophyll Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results are also reported by Hanson et al (2006) [14] and Nasarullah et al (2022) [15] . Further, Reyes et al (2018) [16] observed the reduced cellular turgor leads to reduced CO 2 assimilation under water shortage leading to a slower plant growth and lower photosynthetic rate.…”
Section: Results and Discussion Plant Height And Number Of Leavesmentioning
confidence: 99%
“…Ekinci et al [ 18 ] confirmed that chlorophyll content in spinach leaves decreased under different irrigation levels. However, Reyes et al [ 19 ] stated that if the plants are not subjected to intense drought stress, their chlorophyll content will not be affected, showing the significance of drought intensity on plants, especially spinach.…”
Section: Introductionmentioning
confidence: 99%